PENGARUH PERCEIVED EASE OF USE, PERCEIVED USEFULNESS DAN PERCEIVED SECURITY TERHADAP CONTINUANCE INTENTION TO USE PENGGUNA E-WALLET DANA DI KOTA SEMARANG - Nur Abdillah Akmal; Sari Listyorini; Andi Wijayanto (Universitas Diponegoro, 2025)
Abstract: The increasingly massive development of technology has brought about many changes, especially in the economy. This creates a challenge for companies in the financial sector to produce digital-based innovations. E-wallet DANA is a digital financial service innovation owned by PT Espay Debit Indonesia Koe. There has been a decrease in the number of e-wallet DANA users in the city of Semarang who choose not to continue using DANA e-wallet services. This research aims to determine the influence of perceived ease of use, perceived usefulness and perceived security on the continuance intention to use of e-wallet DANA users. The type of research used is explanatory research with a quantitative approach. Sampling used non-probability sampling with accidental sampling and purposive sampling methods. The sample consisted of 100 respondents who were e-wallet DANA users in Semarang City. Data processing was carried out using SPSS ver 21. This research concludes that perceived ease, perceived usefulness, perceived security, both partially and simultaneously, positively and significantly influence the continuance intention to use of e-wallet DANA users. Keywords: technology acceptance model; perceived ease of use; perceived usefulness; perceived security; continuance intention to use. Abstraksi: Perkembangan teknologi yang semakin masif memberikan banyak perubahan terutama dalam perekonomian. Hal ini menimbulkan suatu tantangan bagi perusahaan di sektor keuangan untuk menghasilkan inovasi berbasis digital. E-wallet DANA merupakan inovasi layanan keuangan digital yang dimiliki PT Espay Debit Indonesia Koe. Terjadi penurunan jumlah pengguna e-wallet DANA di kota Semarang yang memilih untuk tidak melanjutkan menggunakan layanan e-wallet DANA. Penelitian ini bertujuan untuk mengetahui pengaruh perceived ease of use, perceived usefulness dan perceived security terhadap continuance intention to use pengguna e-wallet DANA. Tipe penelitian yang digunakan adalah explanatory research dengan pendekatan kuantitatif. Pengambilan sampel menggunakan non-probability sampling dengan metode aksidental sampling dan purposive sampling. Sampel berjumlah 100 responden yang merupakan pengguna e-wallet DANA di Kota Semarang. Pengolahan data dilakukan menggunakan SPSS ver 21. Penelitian ini menyimpulkan bahwa perceived ease, perceived usefulness perceived security baik secara parsial maupun simultan memengaruhi secara positif dan signifikan terhadap continuance intention to use pengguna e-wallet DANA. Kata Kunci: technology acceptance model; perceived ease of use; perceived usefulness; perceived security; continuance intention to use.